Alleged Predatory Pricing through Flash Sale Practices on the Tiktok Shop Application - Narusweta, Arasyel Noor Vinki; Setiawati, Diana (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
Technological advances have a major impact on the economic sector in this digital era, one of which is the use of digital media for business activities through e-commerce. Initially the TikTok application was a social media application, over time Tiktok developed to present innovative buying and selling activities through Tiktok Shop. The features provided by Tiktok Shop often offer massive promotions in a limited time or what is also known as a flash sale. But unfortunately, the innovation of the flash sale program presented at Tiktok Shop raises issues related to business competition such as the alleged predatory pricing listed in article 20 of Law No. 5 of 1999 (Anti-Monopoly Law) in the Tiktok Shop application. The purpose of this study is to show that it is true that there are allegations of predatory pricing carried out by flash sale practices by business actors in the Tiktok shop and how the role of the KPPU steps in responding to allegations of predatory pricing.The research method used is normative law, using a statutory approach and a legal concept approach, to analyze a legal issue based on primary, secondary and tertiary law. The results of this study indicate that, the practice of flash sales on the Tiktok Shop application automatically cannot be categorized as predatory pricing which can cause monopolistic practices or unfair business competition. This is because the practice of flash sales on Tiktok shop does not fulfill the elements and conditions of predatory pricing in accordance with Law No.5 of 1999. Furthermore, related to this phenomenon, KPPU has not been able to state the truth of predatory pricing that occurred in the Tiktok Shop application due to the absence of incoming reports, KPPU also makes preventive efforts in preventing unfair business competition practices